Viral vector delivery of follistatin enhances recovery of reinnervated muscle. Issue 4 (14th August 2019) - Isaacs, Jonathan; Feger, Mark A.; Mallu, Satya; Yager, Dorne; Shall, Mary; Patel, Gaurangkumar; Protzuk, Omar; Graham, Lindsay
Abstract: Introduction: Poor recovery following nerve repair is due to progressive temporal loss of muscle function. Follistatin (FS), a glycoprotein with anabolic properties, may enhance muscle recovery following reinnervation. Methods: Seventy‐two male Sprague–Dawley rats underwent temporary (3 or 6 month) denervation or sham denervation. After reinnervation, rats were administered adeno‐associated viral vectors expressing FS deoxyribonucleic acid (isoform FS‐317) injected into the target muscle or sham treatment. Final assessment included muscle function testing, muscle histomorphology, nerve histomorphology, and FS protein quantification. Results: FS improved muscle mass and type IIB muscle fiber size, and increased G‐ratios and mean axon diameter in the 6‐month temporary denervation group ( P  < .05). Elevated FS protein levels were detected in treated muscle ( P  < .05). FS increased satellite cell counts following temporary denervation and repair ( P  < .05). Discussion: FS treatment had anabolic, neurotrophic, and satellite cell stimulatory effects when administered following prolonged (6‐month) temporary denervation and repair.